Precipitation forecast on the basin contributing to the La Esperanza reservoir using HadCM3 climate model - Velásquez Intriago, Francisco (2019)
Rainfall forecasts as a hydrological variable indicate the possible amounts of rainfall in a future period. Contemplating the temporal and spatial variation, the objective was to forecast rainfall over the basin contributing to the “La Esperanza” reservoir by applying the HadCM3 global climate model. Through retrospective information, historical rainfall information was analyzed between the years 1980-2017, from 50 rainfall stations near the area under study, using the Excel 2016 software, to synthesize numerical data in the statistical analysis and hydrological data estimation, through the methods: neighborhood averages, normal and regression ratios; from which prospective information was obtained through the use of ArcGIS 10.4.1 software, extracting 456 average precipitations, by means of the isohyets method, obtaining the real observed average precipitations, to which the constants of anomalies of the HadCM3 global climatic model were applied. The results indicate that rainfall in the study area tends to increase in each period of years analyzed: 2010-2039 with 16.75%, 2040-2069 with 47% and 2070-2099 with 80,16% increase with respect observed average real precipitation: 1759.64 mm. The present study proposes a forecasting tool for the entities in charge of water resource planning for decision making.